Modern kentte farklı kadın dindarlıkları : İstanbul örneği - Işık, Zehra (My University, 2020)
MODERN KENTTE FARKLI KADIN DİNDARLIKLARI:İSTANBUL ÖRNEĞİBu çalışmada İstanbul’un Fatih ilçesi merkezli faaliyet gösteren iki dinî gruptaki kadın dindarlığı biçimleri ele alınmıştır. Aralarındaki mekânsal yakınlığa rağmen toplumda birbirinden oldukça farklı dindarlık tezahürleriyle tanınan İsmailağa Cemaati ve Cerrahî Grubu mensubu kadınların dindarlıkları; Gruba bağlanma süreçleri, gruba girdikten sonra yaşanan değişim, din algısı ve dinî yaşantı, modern yaşam ve popüler kültür ürünlerine yönelik tutum ve İslam’da kadının yeriyle ilgili güncel tartışmalı konulara yaklaşım, konu başlıkları çerçevesinde incelenmiştir.Gömülü Teori türlerinden Sistematik Desen’in uygulandığı araştırmada çoklu veri toplama teknikleri kullanılmıştır. Derinlemesine görüşmelerde İsmailağa Cemaati’nden 20, Cerrahî Grubu’ndan 8 olmak üzere toplam 28 kişiyle görüşülmüştür. Her iki grubun faaliyetlerine yaklaşık bir buçuk yıllık süreyle katılımcı gözlemci olarak iştirak edilmiştir. Her iki gruba ait yazılı kaynaklar, medya ve sosyal medyadaki programlar ve paylaşımlar doküman taraması yapılarak incelenmiştir. Veri analizi sonucu ulaşılan kavramsallaştırma ve temalar arası ilişkiler, şemalarla görselleştirilmiştir.Araştırma sonucunda iki teoriye ulaşılmıştır. Teori 1: İslam’da kadının yeriyle ilgili güncel tartışmalı konularda katı-gelenekçi tutuma sahip İsmailağa Cemaati’nde kadın dindarlığı “Çarşaf” merkezli şekillenmektedir. Teori 2: İslam’da kadının yeriyle ilgili güncel tartışmalı konularda kısmen modern-kısmen gelenekçi tutuma sahip Cerrahî Grubu’nda kadın dindarlığı “Tekke” merkezli şekillenmektedir.

DIFFERENT FORMS OF WOMEN RELIGIOSITY IN THE MODERN CITY: ISTANBUL SAMPLEIn this study, the forms of women religiosity in two religious groups based in the Fatih district of Istanbul are discussed. Despite the spatial closeness between them, the religiosity of women of Ismailaga Community and Cerrahi Group, who are known in the society for their appearances of different religiousness: The processes of attachment to the group, the change after entering the group, the perception of religion and religious life, the attitude towards modern life and popular culture products, and the approach to current controversial issues related to the place of women in Islam were examined within the framework of topics.Multiple data collection techniques were used in the study in which Systematic design, one of the Grounded Theory types, was applied. During the in-dept interviews, a total of 28 people were in7terviewed, 20 from Ismailaga Community and 8 from the Cerrahi Group. Participated in the activities of both groups for approximately one and a half year as a participant observer. Written documents, media and social media programs and shares belonging to both groups were examined by scanning documents. The inter-theme relationships and conceptualisations reached as a result of data analysis process are visualised with diagrams.As a result of the research, two theories have been reached. Theory 1: In the Ismailaga Community, which has a solid-traditionalist attitude on current controversial issues regarding the place of women in Islam, women religiosity is based on Carsaf. Theory 2: In the Cerrahi Group, which has a modern-partly traditionalist attitude in current controversial issues about the place of women in Islam, women religiosity is shaped in the center of Tekke.
Keywords: Din; Dindarlık; Dinî Gruplar; Felsefe ve din; Gömülü Teori Women Religiosity; Grounded Theory; Kadın Dindarlığı; Kadınlar; Kent Dindarlığı; Philosophy and religion; Piety; Religion; Religious Groups; Urban Religiosity; Women